Posaconazole Pharmacokinetics in Healthy Cats after Oral and Intravenous Administration - Mawby, D.I. (J Vet Intern Med, 2016)
BACKGROUND: Posaconazole is the most active available azole antifungal drug, but absorption and pharmacokinetics are not available to guide dosing regimens in cats. OBJECTIVE: To determine the pharmacokinetics of posaconazole in cats given an IV solution and PO suspension. ANIMALS: Six healthy, adult research cats. METHODS: After a 12‐hour fast, each cat received 15 mg/kg of posaconazole PO suspension with food. Four cats also received 3 mg/kg IV posaconazole after a 7‐day washout period. Plasma was collected at predetermined intervals for analysis using high‐pressure liquid chromatography (HPLC). Concentration data were analyzed using a 2‐compartment pharmacokinetic analysis for IV administration data and a 1‐compartment analysis with first‐order input for PO administration data using Phoenix(®) software. RESULTS: After IV dosing, volume of distribution (V (SS)) was 1.9 (0.3) L/kg (mean, standard deviation), terminal half‐life (T (½)) was 57.7 (28.4) hours, and clearance was 28.1 (17.3) mL/kg/h. After PO dosing, peak concentration (C (MAX)) was 1.2 (0.5) μg/mL and T (½) was 38.1 (15.0) hours. Bioavailability of PO suspension was 15.9% (8.6). No adverse effects were observed with either route of administration. CONCLUSION AND CLINICAL IMPORTANCE: Despite low PO absorption, these data allow for simulation of PO dosage regimens that could be explored in clinical studies. Two regimens can be considered to maintain targeted trough concentrations of 0.5–0.7 μg/mL as extrapolated from studies in humans: (1) 30 mg/kg PO loading dose followed by 15 mg/kg q48h, or (2) 15 mg/kg PO loading dose followed by 7.5 mg/kg q24h.